STUDI POLA KEMITRAAN USAHA PETERNAKAN AYAM RAS PEDAGING (Broiler) DI DESA GELEBAK DALAM KECAMATAN RAMBUTAN KABUPATEN BANYUASIN - Febriandika, Bayu; Iskandar, Sutarmo; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
Study patterns poultry effort partnership (broiler) at gelebak dalam village regency rambutan district banyuasin. This research is executed to know how partnership pattern among cattleman with PT. Mitra Wijaya Mulia and accounting how big gain which gotten by race chicken cattleman broiler by patterns partnership. This research is executed at Gelebak Dalam Village In Regency Rambutan district Banyuasin on december 2015 until with February 2016. Observational method that is utilized which is method survey. Pull method samples that utilized by deliberate( Puposive is Sampling ), and in this research available 2 example that become its sample unit, which is (1 ) PT. Mitra Wijaya Mulia (Firm Fundamental) and (2 ) Cattlemen (Plasma) with amount 6 cattleman. Methodic data collecting that is utilized is Observation and interview method which is watch / direct interview with respondent utilize questionnaires assistive tool already predetermined and aided with acquired data of relationship aught institutes its with this research. Data processing method and analisis is data that is utilized which is descriptive analytic-method with kualitatif's approaching to answer about problem first, and to answer problem both of utilizes descriptive analisis with mathematical approaching. Result observationaling to point out that, to become partner, a cattleman has to accomplish operational aspect as plasma and can provide technical aspect already been established firm. While PT. Mitra Wijaya Mulia Interrupts me core firm have given the best one service to race poultry effort broiler this. And terminologicals service cattleman already be given firm to cattleman was passably, just just in penyediaan ranch production medium sometimes delay happening, e.g. (DOC, Weft, doctor and vitamin), that all since a lot of it foots up partner cattleman from PT. Mitra Wijaya Mulia that regard medium supply delay ranch production. Gain average which is gotten of chicken breed effort pedaging's race by patterns partnership be as big as Rp. 31.068.829,00/pp. While acquired profit sharing of market price difference, with presentase 70%: 30%, therefore, averagely gain which gotten by core firm as big as Rp. 64.416.577,00/pp with price difference. Rp 2.625/Kg/Pp, meanwhile on a par cattleman gain as big as Rp. 27.607.104,00/pp with price difference. Rp 1.12 /Kg/Pp for each chicken weight kilogram that is marketted. So total acquired average gain cattleman of chicken breed effort broiler race by patterns this partnership as big as Rp. 58.675.933,00/pp.